ANALISIS PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP MENTAL ACCOUNTING DAN TINGKAT KEPUASAN PADA MASYARAKAT DI SUMATERA UTARA - Raudah Azzahra Manurung; Muhammad Lathief Ilhamy Nasution; Nurbaiti (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The purpose of this study was to find out how the influence of using a digital wallet on mental accounting and the level of community satisfaction in North Sumatra. In this survey, using a quantitative descriptive method. The data used in this study are primary data collected through questionnaires from 100 people in North Sumatra with age criteria of 19-24 years. The analysis used is simple linear regression analysis using the IBM SPSS Statistics Version 25 program. Based on the results of the study, it shows that digital wallets have a significant effect on mental accounting and satisfaction levels. Thus, digital wallets make it very easy for people to make transactions. The better the digital wallet application is used, the better the mental accounting and the level of community satisfaction in North Sumatra.